2020
DOI: 10.3390/cryst10050343
|View full text |Cite
|
Sign up to set email alerts
|

The Fracture Behavior and Mechanical Properties of a Support Structure for Additive Manufacturing of Ti-6Al-4V

Abstract: In the laser powder bed fusion processes for metal additive manufacturing, a support structure is needed to fix the part to the base plate and to support overhanging regions. Currently the importance of support structure for a successful build process is often underestimated and some effects are not yet well understood. Therefore, this study investigates the fracture behavior and mechanical properties of thin additive manufactured struts using the titanium alloy Ti-6Al-4V and specific machine parameters for su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Also, since the supports' scanning strategies and geometries are different from the parts, it is assumed that the support material properties might vary. Thus, some studies have been considering tensile testing supports of different geometries [15,16,51] to characterise their behaviour. However, there is still a lack of data that could help AM-engineers to design supports, and standard methods to test these structures repetitively are still required.…”
Section: Support Modelling Approachesmentioning
confidence: 99%
“…Also, since the supports' scanning strategies and geometries are different from the parts, it is assumed that the support material properties might vary. Thus, some studies have been considering tensile testing supports of different geometries [15,16,51] to characterise their behaviour. However, there is still a lack of data that could help AM-engineers to design supports, and standard methods to test these structures repetitively are still required.…”
Section: Support Modelling Approachesmentioning
confidence: 99%
“…However, these parts currently only exist in the study form, which is far from the practical applications in engineering due to the strict criteria in nuclear reactors. The AM metals have the features of building direction, heterogeneities and defects of voids and micro-cracks [34][35][36], which can cause the propagation of cracks and branching which can actively reduce fatigue life tremendously [37][38][39]. A series of microstructures with different morphological and crystallographic features were generated to study the effects of the individual texture on the mechanical properties of the AM stainless steels, which showed that the highest load-bearing capacity of the material occurs when the macroscopic loading acts under an angle of 45…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The first dimension is represented by the defect types and the second dimension by the properties. For example, a reduced cross-section due to porosity has an influence on ultimate tensile strength (Weber et al, 2020b), elongation, Young's modulus and fatigue performance (Stef et al, 2018). Another example of the influence on mechanical properties is surface roughness.…”
Section: Identification Of Defects and Effect On Propertiesmentioning
confidence: 99%